Analisis Pemasaran Sayur Mayur di Desa Alebo Kecamatan Konda Kabupaten Konawe Selatan - Syahputri, Anggi Anggraeni Julianti; Mukhtar, Mukhtar; Geo, La Ode (Department of Agribusiness, Halu Oleo University, 2019)
The purpose of this study was to find out the marketing strategies of vegetables in Alebo Village, find out the revenue from the sale of vegetables and the number of contributions from vegetable farming to the total income of farmer households. This research was conducted in Alebo Village, Konda District, South Konawe Regency. The population in this study were all vegetable farmers in Alebo Village with a total of 150 people. Determination of the sample is done by simple random sampling. Determination of the number of samples using the Slovin formula in Rianse (2009) which is as many as 60 people. The data collected consists of primary data and secondary data. Data analysis using descriptive method is a method that aims to analyze marketing strategies based on marketing mix strategies, namely product, price, place, and promotion, the results of vegetable sales at the Farmer level in Alebo Village Konda Sub-District, South Konawe District and to find out contributions income from vegetable farming to farmers' total income is used percentage formula. The results showed that the marketing strategy of vegetables produced by farmers in Alebo Village was to use a mixed marketing strategy such as the first strategy of product mix was the farmers' strategy on four vegetable products such as kale, spinach, long beans and chili having a product. quality and quantity are determinants and influence competitive advantage in the vegetable industry. Farmers must pay more attention to the characteristics of marketable vegetables. The second strategy of price mix, namely pricing at the level of vegetable farmers in Alebo Village is determined based on market mechanisms. Given the collectors commonly called papalele to have the capital to do marketing and are most able to access the market. the third mixed distribution strategy is the vegetable marketing channel that this farmer has one channel in which producer farmers do vegetable marketing through papalele. And four promotional mix strategies are a form of promotion carried out by vegetable farmers in their products by means of personal sales promotions. Receipt of sales results are often faced with price fluctuations sometimes high even low if low but farmers do not lose. Based on the results of the study, vegetable prices at the time of the study were categorized as normal prices. And vegetables are sold out. The contribution from vegetable farming to the total household income in Alebo village is 88%. This shows that vegetable farming is a source of income that contributes greatly to respondent farmers.